Advertising in a cross-cultural environment: a study of French and Chinese consumers - Simon, Charlotte (2007)
The globalisation of media, incomes and technology was expected as the convergence of homogeneous consumer needs, tastes and lifestyle. However, there is a debate on the fact that culture is universal or not. This paper aim is to research the possibility of initiating a new strategy for advertisement in a cross-cultural environment. By studying the concept of culture and using it to compare the way Chinese and French people consider advertising, this paper wants to outline a new pattern for a new possible strategy away from current strategies of doing nothing on culture or focus too much on it. A literature review outlines the different concepts of culture and help to compare France and China. Thus, it also helps determine in which way a culture impact on marketing in terms of consumer behaviours, country of origin effects and advertising. However, less research has been done on the marketing communication processes in Asia and tends to focus on studying western countries instead. In that case the paper also aims to compare this research on French and Chinese comparison with other research on Chinese and Anglo-Saxon countries. The research determines that like for other countries, cultures from China and France cannot be bond and culture remains a national pattern. However a new similarity has emerged from this study between French and Chinese young people. This similarity is in terms of support and form of the advertisement. From that, the paper is able to provide marketers with new tips on how to handle culture.